2015
DOI: 10.1371/journal.pone.0134534
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cytogenetic Identification of a New Wheat-Rye 6R Chromosome Disomic Addition Line with Powdery Mildew Resistance

Abstract: Rye (Secale cereale L.) possesses many valuable genes that can be used for improving disease resistance, yield and environment adaptation of wheat (Triticum aestivum L.). However, the documented resistance stocks derived from rye is faced severe challenge due to the variation of virulent isolates in the pathogen populations. Therefore, it is necessary to develop desirable germplasm and search for novel resistance gene sources against constantly accumulated variation of the virulent isolates. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…Gallego and Benito (1997) found that Al tolerance is controlled by at least two major dominant and independent loci (Alt1 and Alt3) located on chromosomes 6RS and 4R. Powdery mildew resistance genes were also found on chromosomes 4R and 6R (Heun et al 1990;An et al 2013An et al , 2015.…”
Section: Discussionmentioning
confidence: 98%
“…Gallego and Benito (1997) found that Al tolerance is controlled by at least two major dominant and independent loci (Alt1 and Alt3) located on chromosomes 6RS and 4R. Powdery mildew resistance genes were also found on chromosomes 4R and 6R (Heun et al 1990;An et al 2013An et al , 2015.…”
Section: Discussionmentioning
confidence: 98%
“…Black diamond shapes indicate no template control in wheat breeding. A great number of desirable wheatrye progenies from various rye accession have been developed by distant hybridization and chromosome engineering, such as wheat-rye 6R disomic addition line WR49 carrying powdery mildew resistance derived from rye cultivar German White [37], wheat-rye 1R disomic addition line N9436B carrying powdery mildew resistance derived from rye cultivar Austrian [38], and wheatrye T1RS•1BL translocation lines from Chinese rye cultivar Baili with resistances to stripe rust and powdery mildew and desirable agronomic traits [39]. Compared with addition lines and substitution lines, translocation lines, especially small segment translocation lines carrying desirable traits, are preferred attributing to less linkage drag.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many studies have aimed to identify new resistance genes in the relatives of wheat [41,42]. In previous studies, the resistance genes Pm7, Pm8, Pm17, and Pm20 were identified in rye, and Pm8 was utilized widely, although the effectiveness of its resistance has now been lost [43][44][45]. Pm21, which is located on the short arm of chromosome 6V in Haynaldia villosa (2n = 14, VV) and it is an excellent gene that confers broad-spectrum resistance to powdery mildew in wheat [46].…”
Section: Discussionmentioning
confidence: 99%